Evaluation of performance of Microprocessors of CPU-GPU CUDA architecture and EDA challenges facing Future Microprocessor Design - Numan, Shaikh; Haider, Sayed Sajjad; Rwitobaan, Shaikh; Shakila, Shaikh; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
To increase the processor speed and its respective performance a more streamlined method of approach was required. Electronic Design Automation (EDA) is implemented. This article describes the changes brought about by EDA in the development of microprocessor systems and the challenges faced by EDA currently and in the future. This article will also describe the various tests and experiments conducted on the CUDA architecture based microprocessor and also highlight the overall performance and thermals of the system under such extreme test conditions.